Governance implications of non-GM private standards on poultry meat value chains. Issue 10 (5th October 2015) - Stefano Pascucci, Dr Liesbeth Dries, Professor Konstantinos Karantininis and Professor Gaetano Martino, Dr; Passuello, Francesca; Boccaletti, Stefano; Soregaroli, Claudio
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the governance implications of non-genetically modified (GM) voluntary private standards on the private label poultry meat value chain of the leading Italian retailer. Considered aspects are: first, the organizational practices adopted along the chain to assure effective segregation; second, the changes in the characteristics and governance of the key transaction (meat processor-retailer); finally, what makes the chain economically sustainable. Design/methodology/approach – A picture of the chain is obtained collecting information from the businesses involved; the snowball selection criterion is used in identifying people to interview. Transaction Cost Economics (TCE) is used to conceptualize the organizational changes in the meat processor-retailer transaction; the coherence of expected-actual variations in asset specificity, uncertainty and frequency, as well as of the observed governance with TCE predictions is assessed. Findings – The creation of the non-GM chain required investments by both the key actors involved and the establishment of a partnership based on trust and mutual dependence. The increase in uncertainty coupled with the rise in asset specificity led to higher transaction costs, requiring a shift of the governance structure toward the right side of the market-hierarchy continuum to economize on costs and improve supply chain performance. TCE well explains the changes occurred. The retailer values the return on image as a strategic asset and bears the non-GM extra costs making the chain economically sustainable. Research limitations/implications – The implications of the findings are twofold. First, they help to identify the critical factors for an effective and economically sustainable segregation of non-GM products/raw materials along agro-food value chains. Second, they show how chain actors could adopt tighter governance structures in order to comply with binding technical and quality specifications, economize on transaction costs and improve supply chain performance. Originality/value – Retailer-led private standards used as regulation and enforcement mechanisms in vertical relations, as well as their organizational implications in the governance of transactions between actors in agro-food value chains have received insufficient attention. This research contributes to fill out this gap.